Empirical Analysis of External Debt Exposure to Exchange Rate Risk in Nigeria - Eze, Afamefuna A.; Ogwu, Stephen Obinozie; Obozua, Obehi Destiny; Okolo, Chukwuemeka Valentine (Asian Journal of Economics and Empirical Research, 2021)
The study investigates external debt exposure to exchange rate risk in Nigeria. The Secondary data used were sourced from World Bank Development Indicators for all the variables from the period 1981 to 2019. By employing the Augmented Dickey-Fuller Unit root test and OLS estimation technique, the study found that external debt service payment (EXTDSP), total payment on external debt (TPEXTD), and trade openness (TROP) is significant. While External debt service payment (EXTDSP) and trade openness (TROP) is negatively impacting the exchange rate (EXCHR). TPEXTD has a positive significant impact on EXCHR at a 5% level of significance. The rest of the explanatory variables: external debt stock (EXTDS), gross domestic product growth rate (GDPGR), and real interest rate (RINTR) are all positive and insignificant at all levels of significance. The study, therefore, recommends that the government should go for concessional loans which has low-interest rate and are long-term in nature and as well encourage international trade with other countries of the world.